THE ROLE OF LAUGHTER IN MARK TWAIN'S CLASSIC WORKS (Proceedings of International Conference on Educational Discoveries and Humanities, 2024)
Mark Twain is a famous critical realist writer in the late nineteenth Century. Through combining humor and irony, he makes relentless expose and criticism of the ugly phenomena in American social life. The excellent satirical art in a number of his works showed, not only became an independent school at the time of the American literature, but also had a profound impact on the future of American literature. In this article, the author describe about Mark Twain’s classical novels, specific language and writing techniques from some classical novels of Mark Twain.